2007
DOI: 10.1111/j.1740-0929.2006.00409.x
|View full text |Cite
|
Sign up to set email alerts
|

Major microbiota of lactic acid bacteria from Matsoni, a traditional Georgian fermented milk

Abstract: A total of 26 samples of Matsoni were collected in Georgia. From these samples 80 strains of lactic acid cocci and 173 strains of lactobacilli were isolated. The number of lactic acid bacteria varied between 105 and 1010 colony forming unit (CFU)/mL. All the isolated lactic acid bacteria were thermophilic bacteria that could grow at 45°C. The predominant lactic acid bacteria were Streptococcus thermophilus and Lactobacillus delbrueckii spp. bulgaricus in 25 samples of Matsoni, while Lactobacillus helveticus wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 13 publications
(22 reference statements)
4
12
0
Order By: Relevance
“…This observation may be related to their starter role during the fermentation process (Michaylova et al, 2006). Identical to our results, Uchida et al (2007) reported that L. delbrueckii subsp. bulgaricus accounts for prominent number in Matsoni, a traditional Georgian fermented milk.…”
Section: Identification Of the Lactic Acid Bacteriasupporting
confidence: 77%
“…This observation may be related to their starter role during the fermentation process (Michaylova et al, 2006). Identical to our results, Uchida et al (2007) reported that L. delbrueckii subsp. bulgaricus accounts for prominent number in Matsoni, a traditional Georgian fermented milk.…”
Section: Identification Of the Lactic Acid Bacteriasupporting
confidence: 77%
“…mesenteroides, Leuconostoc pseudomesenteroides, and Streptococcus parauberis were the predominant isolates in fermented mares' milk from Inner Mongolia, in China, by using SDS-PAGE profiling of whole-cell protein and phylogenetic analysis on the basis of 16S rRNA gene sequences for typing and identifying LAB strains. There have also been similar studies on the predominant LAB or yeasts in other traditional dairy products; Dadih in Indonesia (Hosono et al 1989), Amasi in Zimbabwe (Gadaga et al 2000), South African fermented milk (Beukes et al 2001), Kule naoto in Kenya (Mathara et al 2004), fermented raw goat milk in Algeria (Guessas and Kihal 2004), Laban in Lebanon (Chammas et al 2006), Dahi in Bangladesh (Harun-urRashid et al 2007), and Matsoni in Georgia (Uchida et al 2007). However, almost all the previous information available on the microbial composition of the traditional fermented milks prepared by the nomads of the Mongolian region has come from studies performed in Inner Mongolia (in China), but not in Mongolia itself.…”
Section: Introductionmentioning
confidence: 88%
“…bulgaricus and S. thermophilus was also observed in previous studies on Matsoni (Uchida et al . ; Quero et al . ) and other yoghurt‐type fermentations (Bokulich et al .…”
Section: Discussionmentioning
confidence: 99%
“…The peculiar technology to produce Matsoni, which is made from heated or pasteurised milk and then incubated at 35–42 °C, explains the concomitant selection of thermotolerant bacteria like enterococci (Uchida et al . ; Bokulich et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation